Diseño de un sistema de control y monitoreo de aires acondicionados tipo mini split hasta 24.000 BTU/h integrado a IoT (2021)
The air conditioning systems or called HVAC for its acronym in English (Heating, ventilating and air Conditioning) are the cause of up to 40% in domestic energy consumption, this according to the International Energy Agency (IEA). According to studies, the efficiency of these systems is affected by different aspects, such as inadequate maintenance, poor calibration by the end user, and environmental conditions in the region. From this research, it was sought to create a network of devices that would allow to measure, store and visualize data about variables like as electrical and temperature of those systems, in order to know their behavior; This would help in subsequent studies to identify failures, timely maintenance schemes that would help to minimize the environmental impact and the same way reduce costs. The use of IoT has spread to every area of our lives directed by need for control and increased knowledge to create processes that generate better comfort in people's lives and given that we have available data that directly affects the performance of the environment allows to be more efficient taking decisions. It was proposed to design a prototype based on microcontrollers that allowed to analyze different variables of HVAC systems with application to IoT for the subsequent analysis of their behavior, an environment was sought that would allow real-time readings, for this it was decided to make use of the facilities of the Hotel MELVIC to carry out tests and calibrations.